Navigating Workplace Dynamics: A Survey of Workplace Interruptions, Affectivity, and Work-Life Conflict - Ghani, Tuba; Abbas, Javaria; Sarwat, Nosheen (Yugoslav Journal of Operations Research; Online firstDO - 10.2298/YJOR240721021G, 2025)
Workplace interruptions have become increasingly prevalent due to the advancement of mobile communication technologies and changing work practices. Despite the significant impact of work interruptions, the ways in which individuals respond to these disruptions remain largely unexplored. This study, grounded in affective event theory, investigates the sources of workplace interruptions, specifically focusing on receiving phone calls, and examines how these interruptions contribute to work-life conflict through the mediating role of affectivity (positive and negative affect). Data were collected from 250 employees in the banking sector of Pakistan. The findings indicate that receiving calls is positively associated with work-life conflict and that affectivity (both positive and negative) mediates this relationship. These results offer valuable theoretical and practical insights for practitioners and decision-makers aiming to mitigate the negative impacts of workplace interruptions on employees' work-life balance.